Processos adsortivos aplicados à desfluoretação de água subterrânea para abastecimento humano - Oliveira, Robson Alves de (2019)
Fluoride (Fˉ) is an element that is commonly present in groundwater, and that in excessive concentrations may make it unfit for consumption. Contamination of groundwater by fluoride ions may occur through natural processes or due to anthropic activity, with the release of fluoride-containing industrial waste. Excessive intake of fluoride may, in the long run, cause so-called dental and skeletal fluorosis. In addition, ingestion of excess fluoride can also, in severe cases, lead to neurological damage, Alzheimer's disease and cancer. That is why it is fundamental to the de-watering of groundwater for human supply. Adsorption is a prominent technique among the available methodologies for water defluoride, being one of the most efficient in terms of cost, design and operation. In this sense, the main goal of the present study was the application of adsorption to groundwater defluoride for human supply in the State of Rio Grande do Sul. Preliminary tests were carried out for the removal of fluoride from synthetic solutions 5 mg L-1, in which several adsorbent, commercial and alternative. A process of ultrasonic assisted synthesis of an adsorbent based on activated alumina modified with ZnCl2 (AA-ZnCl2) has been proposed. In the characterization step, the adsorbents adsorbents adsorbents adsorbents commercial powder without chemical modification (AACP) and AAZnCl2 were obtained, and BET, EDS scanning electron microscopy, diffraction analysis of Xrays and FT-IR. A procedure was performed to obtain the ideal conditions of the fluoride adsorption process with AA-ZnCl2, using a Central Compound Design for two factors (pH and adsorbent dosage) with response surface methodology. Kinetic and isothermal adsorption tests of fluoride were carried out for AACP and AA-ZnCl2, and the optimum adsorbent conditions proposed for adsorption of groundwater fluoride were obtained. In the preliminary tests AACP it presented fluoride removal efficiencies of 65.4 and 66% for synthetic solutions, and only 38.6% for groundwater. The adsorbent presented the best percentage of removal for both synthetic solutions (> 98%) and groundwater (55.4%). The analysis of the residual concentrations of fluoride, chloride, nitrate, sulfate and phosphate obtained for the synthetic solution of fluoride showed that these parameters meet the maximum permitted value stipulated by the Brazilian standard regulation of potability (Portaria de Consolidação nº 5/2017). The results of the procedure to obtain the ideal conditions of the fluoride adsorption process showed that the two variables, pH and adsorbent dosage, and their interactions on the adsorption capacity are significant at the level of significance adopted. The AA-ZnCl2 exhibited fluoride adsorption property in the pH range of 4 to 10, and the dosage defined as the ideal for the following experiments was 3 g L-1. The results of adsorption kinetics tests showed that AAZnCl2 presented an extremely fast and efficient adsorption. For an initial fluoride concentration of 5 mg L-1, a removal efficiency of 97.4% was achieved with only 5 minutes of contact time, and a fluoride residual of only 0.133 mg L-1 was obtained. The kinetic model of pseudo-second order was the one that most adequately described the kinetics of fluoride adsorption, presenting values of R2 ≥ 0.99. The results of the fluoride adsorption isotherms tests indicated that the Freundlich isotherm model fitted better to the experimental data than the Langmuir isotherm model. After the tests to obtain the optimum adsorbent conditions for adsorption of groundwater fluoride, it is concluded that the ideal dosage, sufficient to reduce the fluoride concentration to the limit established by Annex XX of “Portaria de Consolidação nº 5/2017”, was that of 5 g L- 1. The results showed that the adsorption with ZnCl2-modified activated alumina via ultrasonic assisted synthesis is efficient for the groundwater defluoration for human supply.